Saccharomyces Boulardii and Saccharomyces Cerevisiae Improve Immunity in Broilers Vaccinated Against Pasteurella Multocida and Salmonella Gallinarum - C Von Mühlen; NL Conrad; AP Roll; RC Dias; FPL Leite; CD Corcini; AS Varela Junior; VFB Roll (Brazilian Journal of Poultry Science)
ABSTRACT This study evaluated the impact of dietary Saccharomyces boulardii and Saccharomyces cerevisiae on the immunity of birds vaccinated against Pasteurella multocida and Salmonella gallinarum. A total of 105 male Cobb 500 broilers were divided into four groups: T1 (vaccinated, no supplement, n = 30), T2 (vaccinated, S. boulardii supplement, n = 30), T3 (vaccinated, S. cerevisiae supplement, n = 30), and T4 (non-vaccinated, no supplement, n = 15). Chickens received a corn-soy diet with 1x107 CFU/g of S. boulardii or S. cerevisiae for 42 days. Immune response was assessed by indirect ELISA and leukocyte counts. At 21 days, both supplemented groups showed significantly higher IgY levels than the vaccinated control (p < 0.05). S. boulardii supplementation increased lymphocytes (p = 0.003) and decreased heterophils (p=0.004), while S. cerevisiae had no significant effect. The heterophil/lymphocyte ratio decreased by respectively 23.4% and 32.8% in the S. cerevisiae and S. boulardii groups at 42 days, with no changes at 21 days. These results indicate that S. boulardii and S. cerevisiae can boost immunity and overall health in broilers.